FIGURATIVE LANGUAGES USED IN MOVIE TAGLINES - HEIN WELAN, CLAUDYA (LANGUAGE HORIZON, 2016)
Abstrak Slogan adalahsalahsatubagianterpentingdalamsebuah film. Setiap slogan dalam film memilikigayamerekamasing-masing yang membuat slogan tersebutberbedadari slogan yang lain. Penggunaanmajasbahasasebagaigayapembuatan slogan adalahsalahsatukunciuntukmembuat slogan tersebutberbedadari yang lain dandapatmenarikperhatian para pembaca yang membacanya. Selainitu slogan dalam film dapatmendukungpembentukanmaknadari film tersebut. Artidarisetiap slogan film berbedasatudengan yang lain bergantungpadakonteksdanjenisdari film tersebut. Tujuandaripenelitianiniadalahuntukmenganalisisgayadarimajasbahasadanmakna yang terbentukdarisetiap slogan film. Penelitianinimenggunakanteoritentangmajasbahasadari Perrine (1992) dan multimodal analisisdari O’Halloran (2011). Analisisdokumenmerupakanteknik yang digunakanmenggumpulkan data dalampenelitianini. Penelitianinimenggunakanmetodequalitatifuntukmenganalisis slogan film. Data dalampenelitianiniberupa poster, judul, dan slogan film.Adaduapoinutamadalampenelitianini. Yang pertamaadalahmajasbahasa yang digunakanuntukmenganalisis slogan film. Majas yang digunakandalam slogan film adalahmajarmetafora, alegori, personifikasi, sinekdok, symbol, paradox, hiperbola, dan understatement. Yang keduaadalahmakna yang terbentukdarimajasbahasadalam slogan film. Setiap slogan film memilikimaknanyamasing-masingberdasarkanpadajudul, slogan, gambar, danjenisdari film tersebut. Faktor-Faktortersebutlah yang membentukmaknadalam slogan film. Perbedaanjenisalirandalam film dapatmenimbulkanmakna yang berbedadarisetiao film. Setiap slogan film dibuatuntukmenarikperhatian para penontonuntukmelihat film tersebut Kata kunci:majasbahasa, film, slogan   Abstract Tagline is one part of the movie that has the big role for the movie. Every movie tagline always has their own style that makes them different from each other. Using the figurative language as the style of the tagline is one of the keys to make that tagline different and can attract the audience’s attention. Beside that tagline of the movie also can construct the meaning of the movie. The meaning of the tagline different from one and another depends on the context and the genre of the movie.The aim of this research is to analyze the style of the figurative language and the constructed meaning of every movie tagline. This research uses the theory from the Perrine (1992) about the figurative language and O’Halloran (2011) about the multimodal discourse analysis. Document is the technique to collect the data. This study uses the qualitative method to analyze the data. The data of this study is taken from the cover, title, and the tagline of the movie. There are two main points of the result of this study. The first is the figurative language that is used in the movie tagline. The figurative languages in the movie taglines are metaphor, allegory, personification, synecdoche, paradox, hyperbole, and understatement. Every movie tagline has their own figurative language that can construct the meaning of that tagline based on their title, tagline, picture, and genre. Different genre can cause the different meaning of the tagline. Every movie tagline is made to persuade and attract the audience’s attention to watch the movie. Keywords : figurative languages, movie, tagline.